Lumbar pain and fin swimming - Verni, E.; Prosperi, L.; Lucaccini, C.; Fedele, L.; Beluzzi, R.; Lubich, T. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: It was hypothesised that fin swimming have unique physiopathologic features in particular concerning low back involvement. METHODS: Retrospective study. Setting: elite competitive fin swimmers. Participants: 17 males and 14 females aged from 16 to 23 years. Intervention: piroxicam, sport interruption for a week, proper warming-up and wearing suggestions during out-of-water exercises in the symptomatic group. Absence of intervention in the asymptomatic one. Measures: anthropometric measures (weight, height, legs length discrepancy), isokinetic measures (trunk flexor/extensor ratio) and conventional radiological investigation were taken for all subjects. RESULTS: Low back pain was present in 14 subjects during off season but only 7 referred discomfort in competitive season. 78.5% of symptomatic subjects showed radiological abnormalities while imaging changes were present in 52.9% of the asymptomatic group. Flexor/extensor ratio isokinetically evaluated was less than one in 6 athletes complaining back discomfort. Non steroid medication, physiotherapy, training and wearing cares was suggested. Authors report a pain free return to competition in 57% and a partial resolution in 28% of those symptomatic cases who were not used to training cares (in particular proper "out-of-water" warming up) and wearing precautions (complete wiping and suitable thermic clothing after swimming). CONCLUSIONS: In fin swimming low back pain can be related to the existence of environmental and intrinsic factors. In our series no significant difference in imaging changes was pointed out among asymptomatic or painful athletes. Therefore a cyclic load on the column, in absence of training precautions can make spine abnormalities (in particular schisis, facet derangement and pars lesion) symptomatic.